A Job Well Done: Clients Satisfied With Extension's Service - Tyann M. Haile; Glenn D. Israel (EDIS)
To assess the quality of the service provided by Extension, a customer survey is conducted annually. In 2004, professional staff in eleven counties recorded the names, telephone numbers, and addresses of people who called, visited for educational information, or who attended in-depth programs during the spring or summer. After recording the contact information, a sample of persons from each county was randomly selected to participate in the survey. Clients were contacted by mail or telephone. The information from the survey is used as part of the FCES' ongoing effort to improve program quality and information delivery. This document is AEC 374, one of a series of the Agricultural Education and Communication Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date November 2005.